Exploring and Measuring The Level of Psychological Empowerment (PE) and Organizational Citizenship Behavior (OCB) Among Government Employees- How They Relate Each Other? - Rostika Petrus Boroh; Arsiah Bahron; Sarina Sahfiza Nasser (2018)
This study aims firstly, to measures the level of Psychological Empowerment (PE) and Organizational Citizenship Behavior (OCB) as perceived by federal government staff working in Sabah, and secondly to identify the link between PE and OCB. There are 4 dimensions of PE which are meaning, competence, self-determination and impact while there are 5 dimension of OCB which are altruism, courtesy, civic virtue, sportsmanship and conscientiousness. 145 usable questionnaires were analyzed using the Statistical Package for Social Science (SPSS) and the instruments are deemed reliable with acceptance range of Cronbach alpha values. The level of PE and OCB in general is high. This shows that the government staff in Sabah show high level of PE and OCB in general. The relationship between PE and OCB was also tested and the results show a significant positive relationship between PE and OCB. In other words, it is proven that positive PE results in positive OCB. The implications of the research findings are also discussed in the study.